Phylogenomic analysis of cytochrome P450 multigene family and its differential expression analysis in pepper (Capsicum annuum L.) - Hao, Yupeng; Dong, Zeyu; Zhao, Yongyan; Tang, Wenchen; Wang, Xueqiang; Li, Jun; Wang, Luyao; Hu, Yan; Fang, Lei; Guan, Xueying; Gu, Fenglin; Liu, Ziji; et al. (Frontiers in Plant Science, 2022)
Plant cytochrome P450 is a multifamily enzyme widely involved in biochemical reactions for compounds synthesis of antioxidants, pigments, structural polymers, and defense-related compounds. Pepper (Capsicum annuum L.) is an economically important plant. Comprehensive identification and characterization of P450 genes would provide valuable information on the evolution relationships of genes and functional characteristics. In this study, we identified P450 genes in pepper with the aid of bioinformatics methods to investigate the phylogenetic relation, gene structure, chromosomal localization, duplicated events, and collinearity among Solanaceae species. We identified and classified 478 genes of P450 from the pepper genome into two major clades and nine subfamilies through phylogenetic analysis. Massive duplication events were found in the P450 gene family, which may explain the expansion of the P450 gene family. In addition, we also found that these duplication genes may have undergone strict purification selection during evolution. Gene expression analysis showed that some P450 genes that belong to clan 71 in pepper may play an important role in placenta and pericarp development. Through quantitative real-time polymerase chain reaction and transcriptome analysis, we also found that many P450 genes were related to defensive and phytohormone response in pepper. These findings provide insight for further studies to identify the biological functions of the P450 genes in pepper.